Pituitary volume in patients with panic disorder - Kartalci, Sukru; Dogan, Metin; Unal, Suheyla; Ozcan, A. Cemal; Ozdemir, Serdal; Atmaca, Murad (Pergamon-Elsevier Science Ltd, 2011)
Panic patients have many functional deficiencies in the hypothalamic-pituitary-adrenal (HPA) axis. Previous studies have shown changed pituitary gland volume in some psychiatric disorders that have functional deficiencies in the HPA axis: However, to date no study has evaluated the pituitary gland volume in patients with panic disorder (PD). We investigated the pituitary gland volume in patients with PD (n = 27) and age- and sex-matched healthy controls (n = 27), using 1.5-T magnetic resonance imaging in this study. Analysis showed that patients with PD had significantly smaller pituitary volume compared to healthy subjects. Patients with agoraphobia especially had a significantly smaller pituitary volume than patients without agoraphobia. There was a significant relationship between the pituitary volume and both the severity of symptoms and the illness duration in the patient group. The results show that patients with PD have reduced pituitary volume, which may reflect the functional abnormalities seen in this disorder. These findings may help us better understand the pathology of PD. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Agoraphobia; HPA axis; Magnetic resonance imaging; Panic disorder; Pituitary gland volume